Mapping the Evolution of Local Government Governance Research: Insights from Scopus Data and VOSviewer Visualization - Ismail Abdullah; Rahmat Abd Fatah (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
This study aims to map the evolution of local government governance research using a bibliometric approach based on Scopus data and VOSviewer visualization for the period 2020–2025. The method employed is quantitative bibliometric analysis combined with network analysis of 368 selected articles from an initial dataset of 4,601 documents. The findings reveal a significant increase in publication output, accompanied by a shift in research focus toward digital governance, sustainability governance, and data-driven policy. Two main clusters are identified: participatory governance, which emphasizes public participation, transparency, and accountability; and empirical governance, which focuses on performance, environmental regulation, and economic impacts. These results indicate a paradigm shift from normative approaches toward evidence-based and technology-driven governance. Additionally, the study highlights geographical disparities in knowledge production, with China, the United States, and the United Kingdom dominating the global literature. This research contributes both theoretically and practically by providing a comprehensive mapping of knowledge and serving as a foundation for future governance research and policy development.